1982
DOI: 10.1002/jcp.1041130211
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of transglutaminase activity during rat liver regeneration

Abstract: Transglutaminase and ornithine decarboxylase activities have been assayed at intervals after partial hepatectomy in regenerating liver cells fractionated to obtain nuclear, cytoplasmic-particulate, and cytoplasmic-soluble fractions. Ornithine decarboxylase activity, localized entirely in the cytoplasmic fractions, undergoes a dramatic induction during the first 4 h after partial hepatectomy and remains elevated. This induction is very sensitive to inhibition by cycloheximide and actinomycin D, as previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…The identity of this protein(s) is unknown yet and is currently the subject of further investigations. An early increase in polyamine-protein conjugates selectively in nuclei has been observed during liver regeneration (Remington and Russell, 1982). Our findings therefore indicate that selective alterations in pol yamhe-conjugated proteins may be among the first regulatory events that occur after axonal injury.…”
Section: Discussionsupporting
confidence: 62%
“…The identity of this protein(s) is unknown yet and is currently the subject of further investigations. An early increase in polyamine-protein conjugates selectively in nuclei has been observed during liver regeneration (Remington and Russell, 1982). Our findings therefore indicate that selective alterations in pol yamhe-conjugated proteins may be among the first regulatory events that occur after axonal injury.…”
Section: Discussionsupporting
confidence: 62%
“…28) On the other hand, early studies indicated that hepatic TGase activity increased after partial hepatectomy. 29,30) The increased TGase activity in regenerating liver is not consistent with our and other's findings and is controversial, and no one has ever gave explanations for that. A potential explanation might be obtained by taking account for a zonal difference in TGase activity during regeneration of the liver.…”
contrasting
confidence: 68%
“…The subcellular distri- bution of TG activity is complex. When enzyme activity is assayed in the presence of excess amounts of an exogenous "acceptor protein" (casein), a procedure that probably reveals maximum enzyme activity, the highest specific activity is observed, as in other tissues, in the cytosol (Remington and Russell, 1982), but significant levels of activity are present in the particulate fractions as well. When TG activity is assayed in the absence of exogenous substrate, the "endogenous" activity measured reflects the presence of endogenous acceptor protein substrates that are available for the enzyme.…”
Section: Discussionmentioning
confidence: 99%